Wellbeing and the environment - Davies-Cooper, Rachel; Burton, Elizabeth, 1967-; Cooper, Cary L. (Wellbeing : a complete reference guide, 2014)
Part of the six-volume Wellbeing: A Complete Reference Guide, this volume examines the ways in which the built environment can affect and enhance the wellbeing of society. Explores the effects of environment on wellbeing and provides insight and guidance for designing, creating, or providing environments that improve wellbeingLooks at the social and health issues surrounding sustainable energy and sustainable communities, and how those connect to concepts of wellbeingBrings the evidence base for environmental wellbeing into one volume from across discipli.